Efektivitas Pelayanan Aplikasi Sistem Informasi Kearsipan Dinamis Terintegrasi (Srikandi) di Dinas Perpustakaan dan Kearsipan Kota Pekanbaru - millenia millenia; Harapan Tua RFS (Jurnal Ilmiah Wahana Pendidikan, 2023)
The use of the Srikandi application at the Pekanbaru City Library and Archives Office aims to create an effective and efficient public service process. In the process of using the Srikandi application, there are several inhibiting factors, namely limited human resources for implementing technical guidance, networks that are sometimes unstable and application servers that are still often down when accessed, and the absence of incoming mail notifications that can be received when the application is not opened. This study aims to determine the effectiveness of Srikandi application services carried out by the Pekanbaru City Library and Archives Office. The theoretical concept that researchers use is the theory of effectiveness by Duncan in Ismaya et al (2021), namely goal achievement, integration, and adaptation. By using descriptive qualitative research methods and data collection techniques based on interviews, observations, and documentation. The results of the research that researchers can get are that the implementation of Srikandi application services still has several factors that become obstacles experienced by the Pekanbaru City Library and Archives Office, so that the Srikandi application services implemented have not been effective.